How can green finance promote the synergistic development of agricultural ecological environment and productivity? - Liu, Liangcan; Li, Xiang; Li, Kaichao (Frontiers in Sustainable Food Systems, 2025)
IntroductionBy maintaining soil health and optimizing water resources management, agricultural ecological total factor productivity (AETFP) builds a basic defense line of safe food supply and environmental balance, effectively reduce the spread of chemical pollution and improve the quality of nutrition supply, thus providing a strategic fulcrum for the management of public health sources.MethodsBased on the provincial panel data of China from 2012 to 2022, AETFP was estimated using EBM-GML model by incorporating the agricultural ecological value into the desirable output, and the influence mechanism of green finance on the AETFP was discussed by using fixed effect model and spatial econometric model.ResultsThe AETFP in all regions of China was steadily improving, especially in the eastern region. Green finance not only promotes the improvement of AETFP in local and surrounding areas, but also improves AETFP by improving agricultural industrial agglomeration. Heterogeneity analysis shows that the promotion effect of green finance is particularly obvious in eastern regions, major grain-producing regions and regions with high digital infrastructure.DiscussionThis study provides empirical support for the paradigm transformation of agroecosystem governance from end-treatment to source prevention and control.